Conventional (bone-type) giant cell tumor of the larynx: the first case with proven H3-3A: c.103G >T (p.Gly35Trp) mutation - Laco, Jan; Vosmikova, Hana; Satankova, Jana; Dedkova, Jana; Mejzlik, Jan; Chrobok, Viktor; Agaimy, Abbas (Virchows Archiv, 2024)
This report documents the first case of a conventional (bone-type) giant cell tumor of the larynx, in which the diagnosis was confirmed by molecular genetic analysis. A 50-year-old non-smoking man experienced progressive hoarseness lasting for 3 months. Imaging showed a 40-mm tumor arising from the right thyroid cartilage. The total laryngectomy was performed. Grossly, the tumor was solid and whitish, with areas of hemorrhage. Microscopically, the tumor consisted of a biphasic population with mononuclear cells with round to oval nuclei, small nucleoli, and pale eosinophilic cytoplasm admixed with evenly distributed dispersed osteoclast-like giant cells. Immunohistochemically, the neoplastic mononuclear cells expressed diffusely vimentin and p63 and focally SATB2. Admixed mononuclear histiocytes coexpressed CD68 and CD163, while the osteoclast-like giant cells showed only CD68 expression. Most importantly, all mononuclear tumor cells showed strong nuclear expression of anti-histone H3.3 G34W antibody. Subsequent next-generation sequencing confirmed the missense mutation of gene H3-3A: c.103G>T (p.Gly35Trp).
Keywords: Larynx; Histone; Molecular genotyping; Giant cell tumor